Bioactive and Therapeutic Dental Materials - Sauro, Salvatore (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book focus principally on ions-releasing and other smart dental materials for application in preventive and restorative dentistry, as well as in endodontics in the form of adhesives, resin-based composites, pastes, varnishes, liners and dental cements. Special attention has been given to bioactive materials developed to induce cells differentiation/stimulation, hard tissue formation and exert antimicrobial actions. New innovations are necessary to continue to help reinforcing existing technologies and to introduce new paradigms for treating dental disease and restoring teeth seriously compromised by caries lesions via biomimetic and more biological operative approaches. Dental bioactive materials is arguably the latest research area in dentistry and thus the amount of new research is overwhelming. However, in this day and age of evidence based practice it important for this new information to be distilled into a practical and understandable format.